MOBILE PHONE USE AND SAFETY: WAYS TO REDUCE THE RISK OF INJURY DURING SPORTS AND EXERCISE - Eremin A.M.; Masyagina N.V.; Martynenko I.V.; Kireeva A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine measures aimed at preventing injuries associated with the use of mobile communications during training sessions. Methods and structure of the study. The information base for the study was the laws and regulations of the Russian Federation, professional standards, statistical data from foreign organizations (NIOSH, OSHA, HSE), data from the All-Russian Research Institute of Labor of the Ministry of Labor of Russia, reflecting the main causes of injuries associated with the use of mobile communications, as well as an analysis of cases of injuries resulting from the use of mobile devices during training sessions in sports schools in Moscow. Results and conclusions. The ways of preventing injuries due to the use of mobile communications during training sessions were determined, which are associated with improving the regulatory framework, expanding the knowledge of teachers about ways to prevent threats with the conscientious performance of their job responsibilities, as well as regular advanced training of employees of sports organizations. In the future, it is necessary to develop local regulations aimed at limiting the use of mobile devices during training sessions. All of the above measures will improve the safety of training, minimize the risk of injury, and increase the level of responsibility of specialists working in the field of physical education and sports.